Digitization, Trust and SMEs - Anna Wziątek-Staśko; Karolina Pobiedzińska (Routledge, 2024)
This book exposes two inspiring research categories: digitization and trust. Digitization is a phenomenon that dynamically modifies the modern world in almost every area. Modern technologies, artificial intelligence and humanoid robots are instruments with an increasingly significant impact on the shape of the management process of modern organizations, including the way people are managed. Trust is a subtle concept, with a very different interpretation, influencing the behaviour of employees in a multifaceted way. A superficial look at the combination of both categories seems to see them as irrational. Upon closer examination, however, it exposes many interesting fields of scientific exploration. Trust, as a research category, has been included in three significant dimensions: in relation to co-workers, superiors and information technology, dominated by digitization. Each draws attention to different problems of priority importance for the organization. Asserting the idea that trust in the conditions of digitization becomes a category of timeless importance in the interdisciplinary dimension, this volume will be of interest to researchers, academics, practitioners and advanced students in the fields of management of technology and innovation, organizational studies and leadership.
Keywords: 650; Trust; Digitalization; Technology; Trust Management; SME Sector; Innovation; Human Capital Management; Leadership; Efficiency; Organizational Culture